GASTRONOMIC CODE IN UZBEK FOLK PROVERBS: LINGUOCULTURAL AND AXIOLOGICAL ASPECTS - Rakhmatilloyeva Feruza Nematilloyevna (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines gastronomic units (gastronyms) in Uzbek folk proverbs from a linguocultural and axiological perspective. The study is based on a corpus of 760 Uzbek proverbs containing gastronomic components. It clarifies the notion of the gastronomic code, distinguishes the gastronym from related terms, and analyzes how food-related lexemes function in proverbs as carriers of cultural meaning and value judgement. The analysis demonstrates that in proverbs gastronyms move from their literal, object meaning to a symbolic-conceptual one: bread (non) expresses the concepts of sustenance, honesty and sacredness; pilaf (osh) — hospitality and solidarity; salt (tuz) — loyalty and gratitude; milk (sut) — purity and motherhood. Statistically, the most active gastronyms are osh (208 proverbs), non (89), milk (32), salt (29) and meat (28). The findings show that gastronyms in Uzbek proverbs predominantly carry positive axiological evaluation, which reflects the sacred status of food in the Uzbek worldview. The study contributes to Uzbek paremiology and linguoculturology by offering a combined statistical and linguocultural description of gastronomic units in proverbs, a field previously studied mainly on phraseological rather than paremiological material.